Detection of staphylococcus aureus using magnetic nanoparticles and surface-enhanced raman spectroscopy - Yong, Yvonne Su Juan (2015)
This project mainly focus on the process of detecting of Staphylococcus Aureus (S.Aureus) via Surface Enhanced Raman Scattering (SERS) and affinity magnetic separation. In which immobilized Vancomycin which behave as a small molecule probe along with Raman dye and PEG were attached on to surface of IO@PDA@Au nanosphere for recognition. Fe3O4 of approximately 10nm were synthesized by the co-precipitation technique, following by the miniemulsion polymerization with polystyrene (PS) and the IO@PS nanosphere of 100nm were obtained. A layer of polydopomine (PDA) was then coated onto IO@PS. Due to the strong interaction between gold and IO@PDA,the formation of IO@PDA@Au shell of 150nm were obtained. After which, both the Raman dye and PEG together with Vancomyin were immobilized onto surface of IO@PDA@Au by thiol bond. The aggregation of gold coated nanosphere after magnetic separation greatly improved the SERS signal whereby the results of the Raman spectra could detect and identify targeted bacteria. S.Aures was captured by the magnetic nanosphere as seen from SEM image, then detection via SERS. And through the SERS spectra, the Raman spectra confirms the presence of S.Aureus. Thus, the presence of S.Aureus is very much dependent on the SERS spectra as it provides the unique Raman spectra that reflects the indication of S.Aureus. By using the respective affinity probe, Raman spectra could aid in detection of different types of bacteria.